Agricultural finance statistics. - United States Department of Agriculture ([Washington, U.S. Govt. Print. Off.], 1962)
This book is a review of agricultural finances in relation to various progresses by farmers in term of financial position and it consequence to the growth of states in the United state.
asm; 15/02/19
Loans
Keywords: Agricultural credit; Agricultural finance; United States